Volatile functionality in action : methods, techniques and assessment - Frajberg, Darián
One of the main features of most Web applications today is their great dynamism. They are undoubtedly characterized by a continuous evolution. After implementing and performing the first deployment of a Web application, some new requirements are bound to arise, which involve the need to incorporate new functionalities, generally unknown during the design stage. This type of functionalities, which arise as a response to unexpected requirements of the business layer, have the peculiarity that they eventually need to be removed due to the expiration of their commercial value. The continuous incorporation and removal of these functionalities, which we will call "volatile functionalities", usually has a negative impact on some important aspects of the Web application. Volatile Functionality meta-framework is a conceptual framework that permits to support the lifespan of volatile functionalities in Web applications. We have developed diverse techniques enabling full support of volatile functionalities for enterprise application. Moreover, we have performed an evaluation for assessing developers experience and solutions performance.